On-line information system for Faculty of Electrical Engineering laboratories / Mohammad Shahrin Mandalam - Mandalam, Mohammad Shahrin (2000)
Web based application is indeed the most widely used technology today. The Web offers so much option that it becomes the single most used information bank in the world. With its ever-expanding technology, there is virtually no limit to what it may offer. This project deals with creating an on-line information system for laboratory to be utilized by students. The software used in developing this project are HTML and ASP.